2004
DOI: 10.1007/bf03325042
|View full text |Cite
|
Sign up to set email alerts
|

New interdisciplinary cognitive-behavioural-nutritional approach to obesity treatment: A 5-year follow-up study

Abstract: As a whole, these results show the efficacy of an interdisciplinary approach to the long-term treatment of morbidly obese patients. It is likely that an outpatient psychological follow-up would have improved this therapeutic success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 26 publications
2
26
3
3
Order By: Relevance
“…The creation of a complex model of therapeutic education is often required by numerous authors of the meta-analyses we analysed and we propose a model in 5 dimensions [2]. An interdisciplinary, multidimensional TPE program showed that more than 50% of participants maintained their body weight at 5 years [39]. A combination between a inhospital and ambulatory follow-up seems to show more satisfactory results in the long-term [40].…”
Section: Discussionmentioning
confidence: 99%
“…The creation of a complex model of therapeutic education is often required by numerous authors of the meta-analyses we analysed and we propose a model in 5 dimensions [2]. An interdisciplinary, multidimensional TPE program showed that more than 50% of participants maintained their body weight at 5 years [39]. A combination between a inhospital and ambulatory follow-up seems to show more satisfactory results in the long-term [40].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several researches have shown that, compared to a purely dietetic approach, a better improvement in the eating behavioural disorders is observed when cognitive-behavioural therapies are associated with a nutritional approach [11][12][13]. A study from our group demonstrated that a 1-day motivational workshop significantly increased regular physical activity among obese patients, thus reducing the risk of obesity relapse [14].…”
Section: Introductionmentioning
confidence: 93%
“…Patients gave their written informed consent. Before study entry, patients had a multiple multi-disciplinary patient educational approach previously described [12,13,15], including diet, physical activity, cognitive behavioural treatment, and/or Orlistat prescription.…”
Section: Methodsmentioning
confidence: 99%
“…A five-year follow-up study where interdisciplinary cognitive behavioural techniques, restrictions in nutrition, daily physical exercise, and relaxation sessions where used, found that 45% of individuals had either lost weight or maintained their weight. The remainder of the individuals (55%) had regained their weight or even weighed more than at their starting point [14]. Another five-year follow-up study with persons in the third age found that a new psycho-pedagogic approach (self-control, cognitive restructuring reinforcement, and relapse prevention) was successful; 70% of the patients lost weight or maintained their weight loss [15].…”
Section: Introductionmentioning
confidence: 99%